Fortress of empire : Spanish colonial fortifications of the Philippines, 1565-1898 - Javellana, Rene B.; Tan, Jose Ma. Lorenzo P. (Makati City, Philippines : Bookmark, 1997)
This is a story of peoples at odds and finding the solution extermination.
1. Safety -- 2. Beginnings -- 3. Pirates -- Defense Net -- 5. People & Personnel -- 6. Fortress of Empire.
Includes bibliographical references and index.
Keywords: FORTIFICATION